Rheological properties of sweet potato starch-date syrup gel - Abdellatif Abdelhakim MOHAMED (Food Science and Technology)
Abstract Date syrup (DS), sugars (SG) and sweet potato starch (SPS) composites were investigated using dynamic rheometry, rapid visco-amylograph (RVA), and texture analysis (TPA). HPLC analysis revealed that DS sugar composition was 55% glucose and 45% fructose. Starch gels (0% to 50% DS or SG) were precooked in RVA. SPS starch gel is considered elastic because the elastic modulus (G`) was much greater than the viscous modulus (G``). The comparison between the effect of DS versus SG revealed differences on the peak viscosity, setback, G` and G``, complex viscosity (η*), tan δ, and gel hardness. The decline in complex viscosity (η*) indicates shear thinning behavior. Despite the similarity in sugar content between DS and SG, as shown by the HPLC analysis, the data presented here disclosed how DS had more impact on the pasting and rheological properties of sweet potato starch compared to SG.